Efficacy and Safety of Bioabsorbable Bone Hemostatic Agent in Total Knee Arthroplasty: A Prospective Randomized Controlled Trial - Kim, Jong-Keun (Clin Appl Thromb Hemost, 2021)
Although a bioabsorbable bone hemostatic agent (BBHA) was developed approximately 20 years ago to overcome the shortcomings of conventional bone wax, its bleeding control capacity has not yet been studied. This study was aimed at investigating the efficacy and safety of BBHA in total knee arthroplasty (TKA). Sixty-two patients who underwent unilateral primary TKA for knee osteoarthritis were included and randomized to the control or BBHA group. Before releasing the tourniquet, BBHA was applied on the bone-cut surface that was not covered by implants. The primary variable was the drainage volume during the postoperative period. The secondary outcomes were total estimated blood loss (EBL), hemoglobin level, hematocrit level, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) level, range of motion (ROM), pain visual analog scale (VAS) score, and rate of complications. There were no significant differences in drainage volume or EBL between the 2 groups. Hemoglobin and hematocrit levels were higher in the BBHA group during the 4-week postoperative period; however, the intergroup differences were not significant. The ESR, CRP, ROM, and pain VAS scores in the BBHA group were not significantly different from the corresponding values in the control group. No specific complications were observed. Although BBHA was found to be safe without complications, it did not decrease bleeding after TKA in general cases. Further studies are necessary to evaluate the efficacy of BBHA in patients with coagulation problems.